2004
DOI: 10.1099/mic.0.27193-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure in a thermophilic anaerobic hybrid reactor degrading terephthalate

Abstract: A thermophilic terephthalate-degrading methanogenic consortium was successfully enriched for 272 days in an anaerobic hybrid reactor, and the microbial structure was characterized using terminal RFLPs, clone libraries and fluorescence in-situ hybridization with rRNA-targeted oligonucleotide probes. All the results suggested that Methanothrix thermophila-related methanogens, Desulfotomaculum-related bacterial populations in the Gram-positive low-G+C group, and OP5-related populations were the key members respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
83
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 50 publications
4
83
1
1
Order By: Relevance
“…Using the 16S rRNA gene and McrA gene as biomarkers, temperature-dependent variations were also observed with acetoclastic methanogen populations found in the order Methanosarcinales (Supplementary Figure 4). The hydrogenotrophic methanogens identified here are closely related to methanogens found in mesophilic and thermophilic TA-degrading reactors (Wu et al, 2001;Chen et al, 2004), and together with Methanolinea tarda NOBI-1 recently isolated from anaerobic digestion processes (Imachi et al, 2008), form a novel cluster separate from other known hydrogenotrophic methanogens. The comparison of McrA genes further suggests that the methanogens found in the new cluster are likely different from M. tarda NOBI-1 (Supplementary Figure 4B). )…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Using the 16S rRNA gene and McrA gene as biomarkers, temperature-dependent variations were also observed with acetoclastic methanogen populations found in the order Methanosarcinales (Supplementary Figure 4). The hydrogenotrophic methanogens identified here are closely related to methanogens found in mesophilic and thermophilic TA-degrading reactors (Wu et al, 2001;Chen et al, 2004), and together with Methanolinea tarda NOBI-1 recently isolated from anaerobic digestion processes (Imachi et al, 2008), form a novel cluster separate from other known hydrogenotrophic methanogens. The comparison of McrA genes further suggests that the methanogens found in the new cluster are likely different from M. tarda NOBI-1 (Supplementary Figure 4B). )…”
mentioning
confidence: 93%
“…Several studies have investigated the microbial populations present in methanogenic TA degradation, often using laboratory-scale reactors operated at various temperatures (Kleerebezem et al, 1999;Wu et al, 2001;Chen et al, 2004). Using ribosomal RNA (rRNA)-based molecular methods, these studies have found that TA-degrading consortia in bioreactors are dominated by two to three bacterial populations and two types of methanogens (Wu et al, 2001;Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations